About “Veshnee Vesel’e” by Vyach. Ivanov — Translation from the Poem “The Seasons” (“Metai”) by K. Donelaitis - Elmira K. Alexandrova (Studia Litterarum)
The article is devoted to the history of the poem “Spring Fun” (“Veshnee vesel’e”), which is an incomplete transcription of the first song from the poem of the Lithuanian poet Kristijonas Donelaitis (1714–1780) “The Seasons” (“Metai”), made by Vyach. Ivanov. The translation was made for the unpublished “Collection of Lithuanian Literature” (prepared at the “Parus” publishing house in 1915–1917), edited by Y. Baltrushaitis and M. Gorky. At the same time, Baltrushaitis acted as an editor-compiler and translator of a collection of Lithuanian folklore for M. and S. Sabashnikov’s publishing house. This project was also not implemented. The correspondence between Vyach. Ivanov, Y. Baltrushaitis and M. Sabashnikov allows to reconstruct the history of translation of the poem. The article provides information about the first publications of separate fragments of the translation (by J. Jasinyavicius in 1963 and T. Venclova in 1978), based on unauthorized typewriting from the Department of Manuscripts of the Institute of Lithuanian Literature and Folklore (Vilnius). The appendix presents Ivanov’s translation according to an autograph from the Manuscript Department of the Institute of Russian Literature (Pushkin House) of the Russian Academy of Sciences. The work is mainly based on archival materials from St. Petersburg, Moscow, Rome, Vilnius.